SEMINAR ASSIGNMENT IN MATHEMATICS AND IT TOOLS - ORSZAGHOVA, Dana (Trends in education, 2009)
Tools of information technology are important means for implementation of elearning. Except of various forms of presentation of mathematical study materials through information technology a feedback is very important - electronic testing and evaluation of acquired knowledge. The main aim of this paper is a brief description and analysis of the possibilities of using information technology tools for entering and elaborating of seminar assignment in electronic form. The main source for the article was formed from experience, achieved from the teaching of mathematics at the Faculty of Economics and Management of the Slovak University of Agriculture in Nitra.
Keywords: mathematics; teaching of mathematics; seminar assignment; e-learning; LMS MOODLE.